1999
DOI: 10.1007/s002219900293
|View full text |Cite
|
Sign up to set email alerts
|

Visual feedback about time estimation is related to a right hemisphere activation measured by PET

Abstract: In previous EEG experiments we have presented a time estimation task to our subjects, who had to press a button with either the left or right index finger 3 s after an auditory warning stimulus (WS). Two seconds later a visual Knowledge of Results (KR) stimulus was presented on a screen in front, informing them about whether the movement had been made in the correct time window (a vertical line), whether it was too early (a minus sign) or too late (a plus sign). The potential distribution underlying the antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 3 publications
7
45
0
Order By: Relevance
“…These findings argue for a general role of these three regions in cognitively controlled time measurement, supporting the conclusions of other authors who have examined similar tasks (Brunia et al, 2000;Coull et al, 2000;Coull and Nobre, 1998;Jueptner et al, 1996;Maquet et al, 1996;Rao et al, 2001;Roland et al, 1981;Tracy et al, 2000;Schubotz and von Cramon, 2001a,b;Schubotz et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings argue for a general role of these three regions in cognitively controlled time measurement, supporting the conclusions of other authors who have examined similar tasks (Brunia et al, 2000;Coull et al, 2000;Coull and Nobre, 1998;Jueptner et al, 1996;Maquet et al, 1996;Rao et al, 2001;Roland et al, 1981;Tracy et al, 2000;Schubotz and von Cramon, 2001a,b;Schubotz et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…These results imply that continuous timing can be performed more or less automatically by a subsection of the motor system, while discrete timing requires more cognitively controlled processing, especially when the intervals measured are one second or longer, and draws on the right prefrontal and parietal cortices. When studies specifically investigating discrete timing are examined as a group, a pattern characterised by right hemispheric activity in the prefrontal and parietal cortices emerges (Coull et al, 2000(Coull et al, , 2004bPouthas et al, 2005a;Lewis and Miall, 2002;Brunia et al, 2000;Coull and Nobre, 1998;Jueptner et al, 1996;Maquet et al, 1996;Rao et al, 2001;Roland et al, 1981;Tracy et al, 2000). Recent work with transcranial magnetic stimulation (TMS) has further supported the involvement of right dorsolateral prefrontal cortex in this type of task (Jones et al, 2004;Koch et al, 2003).…”
mentioning
confidence: 99%
“…Consequently, it has been proposed that the principal anatomical structures affected by these disorders, namely the cerebellum and basal ganglia, must be crucial to the effective running of an "internal clock" (Ivry, 1996). The involvement of the cerebellum and basal ganglia in motor and perceptual timing has been confirmed by imaging studies using various timing tasks, such as the repetitive tapping paradigm (Lejeune et al, 1997;Rao et al, 1997;Rubia et al, 1998), duration discrimination (Jueptner et al, 1995;Maquet et al, 1996;Rao et al, 2001;Ferrandez et al, 2003;Miall, 2003a, 2006;Nenadic et al, 2003;Harrington et al, 2004a), velocity discrimination (Jueptner et al, 1996), rhythm discrimination (Schubotz et al, 2000;Schubotz and von Cramon, 2001), temporal discrimination (Pastor et al, 2006), and time production and reproduction (Brunia et al, 2000;Tracy et al, 2000;Miall, 2002, 2006;Macar et al, 2002Macar et al, , 2004Pouthas et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…In the present study, the PFC, which could be associated with enhancement of torque exerted during MVC, was measured as a cortical region measurement by NIRS based on the knowledge from previous studies (Brunia et al, 2000;Kawashima et al, 2000). As a result, the right field of the PFC was found to be activated under the VFB condition.…”
Section: Future Prospectsmentioning
confidence: 87%
“…Kawashima et al (2000) reported that when subjects received appropriate feedback information and those that did not after line drawing tasks were measured for cerebral activity by positron emission tomography (PET), the latter subjects exhibited activated PFC along with improved accuracy of the line drawing task. Brunia et al (2000) reported that subjects who were presented feedback information improved accuracy of button press timing, simultaneously PFC was activated compared with control subjects.From the findings of these previous studies, it is assumed that muscle force is enhanced by MVC when feedback information is presented and this enhancement is associated with the PFC. Thus, the present study measured muscle force on MVC tasks with visual feedback of exerted force.…”
mentioning
confidence: 99%